An inductive thematic analysis of female competitive figure skaters` experiences of weight pressure in sport - Voelker, D. K.; Reel, J. J. (Journal of Clinical Sport Psychology, 2015)
In this study, the authors examined female competitive figure skaters` experiences of weight pressure in sport. Perceptions of the ideal skating body; sources of weight pressure; ways that body image, weight-management behaviors, and athletic performance have been affected; and recommendations for improving body image were explored. Aligning with a social constructivist view (Creswell, 2014), data were analyzed using an inductive thematic approach (Braun & Clarke, 2006). Skaters described the ideal skating body in an inflexible fashion with little room for deviation and acceptance of body diversity. Skaters cited their first weightpressure experience between 7 and 14 years of age, which most notably involved coaches, parents, skating partners, and other aspects of the skating culture. These experiences were characterized as promoting body-image concerns, unhealthy weight-management strategies, and interference with the psychological aspects of on-ice performance. Results from this study demonstrate the need to construct and maintain body-positive skating environments.